Evaluation of Threats Occurring During Provision of Road Transport Services in the EU Territory by Small and Medium-Sized Companies from Poland - Marek Krzywonos (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2020)
The aim of the paper is to conduct an analysis of various threats that may occur during road freight transport in the territory of the European Union. The research method consisted of a survey and the sample group selected for the survey were transport companies from eastern and southern Poland. The paper presents the current condition of Polish transport companies on the EU market and various threats that may occur while delivering road freight transport services. Polish carriers make a considerable contribution to international road freight and cabotage operations and Polish drivers constitute 9,99% of all employed in the industry in the EU. In 2016 Polish carriers delivered road freight services using 205,390 lorries. When it comes to threats, recent years brought about the emergence of new threats related to terrorism and mass migration. These threats constitute new challenges for Polish transport companies. Therefore, it would be a good idea to develop a model of good practices (recommendations) which would lead to improvements in the level of security during the process of rendering transport services.